1997
DOI: 10.1111/j.1365-2788.1997.tb00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition as a function of social connpetence and depressed mood in Individuals with intellectual disability

Abstract: The present study was designed to test whether social competence and mood were predictive of the performance by adults with mild or moderate intellectual disability on a matching-to-sample task using facially expressed emotions as stimuli. Thirty-eight subjects were assigned to either a depressed mood group or a non-depressed mood group based on their scores on the two depression sub-scales of the Reiss Screen for Maladaptive Behavior. The groups were matched on sex, age and level of intellectual disability. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Our results indicate a general bias towards viewing neutral faces as sad, which is consistent with previous investigations that have reported that, when a neutral face is mislabeled, it is often considered sad (Gur et al, 2002;Rojahn et al, 1997). Some investigators have suggested that the context in which neutral faces are presented can influence judgment so that neutral faces presented among happy faces are considered sad (Russell, 1991).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicate a general bias towards viewing neutral faces as sad, which is consistent with previous investigations that have reported that, when a neutral face is mislabeled, it is often considered sad (Gur et al, 2002;Rojahn et al, 1997). Some investigators have suggested that the context in which neutral faces are presented can influence judgment so that neutral faces presented among happy faces are considered sad (Russell, 1991).…”
Section: Discussionsupporting
confidence: 92%
“…This is an inevitable consequence of studying emotional bias in perception. However, a previous study in which neutral was a response option (Rojahn and Warren, 1997) reported that when participants mislabeled the emotion, there was a bias towards negative affect (i.e., sad or angry).…”
Section: Discussionmentioning
confidence: 98%
“…The assessment of social skills have been applied to various populations such as those with schizophrenia, anxiety, intellectual disabilities, autism, sensory impairments, depression, learning disabilities, emotional disturbance, as well as typically developing children (Agaliotis & Kalyva, 2008;Garland & Fitzgerald, 1998;Matson, 1990;Rojahn & Warren, 1997). More recently, the assessment of social skills has expanded to individuals with medical conditions, including epilepsy, spina bifida, and chronic illness Matson, Luke, & Mayville, 2004;Meijer, Sinnema, Bijstra, Mellenbergh, & Wolters, 2000;.…”
Section: History Of Assessmentmentioning
confidence: 99%
“…Furthermore, disruption to emotion perception appears to play a role in a variety of clinical disorders, such as autism (Bolte & Poustka, 2003;Humphreys et al, 2007;Lindner & Rosen, 2006;Mazefsky & Oswald, 2007), schizophrenia (Edwards et al, 2002;Mandal et al, 1998;Tremeau, 2006), attention-deficit hyperactivity disorder (ADHD) in children (Kats-Gold et al, 2007;Pelc et al, 2006), intellectual disability (Rojahn & Warren, 1997;Williams et al, 2005;Wishart et al, 2007), and anxiety disorders (panic disorder, Kessler et al, 2007;obsessive-compulsive disorder, Aigner et al, 2007;social anxiety, Montagne et al, 2006). Indeed, evidence from clinical groups [e.g., TBI (Watts & Douglas, 2006), schizophrenia (Hooker & Park, 2002;Kee et al, 2003;Morrison & Bellack, 1981;Mueser et al, 1996;Sergi et al, 2006), autism (Boraston et al, 2007), and children with ADHD characteristics (Kats-Gold et al, 2007)] mirrors studies of normal adults in suggesting that those who are poor at reading affective information demonstrate low levels of social skills and0or social functioning.…”
Section: The Significance Of Emotion Perceptionmentioning
confidence: 99%